2012
DOI: 10.4236/ijoc.2012.21014
|View full text |Cite
|
Sign up to set email alerts
|

Surface Tension, Density and Viscosity Studies on the Associative Behaviour of Oxyethylene-Oxybutylene Diblock Copolymers in Water at Different Temperatures

Abstract: The associative properties of methoxy (CH 3 O-) ended E 58 B 11 and hydroxyl (-OH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…These improvements in emulsion formation and stability for ultrasound treated proteins were associated with increases in hydrophobicity, which occurred as hydrophobic protein residues within the interior of the untreated aggregate became revealed upon treatment with ultrasound, and improved interfacial packing at the emulsion droplet interface. O'Sullivan, Park, et al, (2016a) observed a significant reduction in the hydrodynamic volume of potato protein isolate which is associated to an increase in the hydrophobicity of proteins (Khan, et al, 2012), accounting for the observed enhancements in emulsion formation and stability in this instance. In addition, ultrasound treatment of whey protein Gülseren, et al, 2007), soy protein Hu, et al, 2013), black bean protein and egg white protein increased the hydrophobicity, and the rate of protein adsorption to and interfacial packing at the oil-water interface, as measured by interfacial tension.…”
Section: Emulsifying Effects Of Ultrasonic Processingmentioning
confidence: 89%
“…These improvements in emulsion formation and stability for ultrasound treated proteins were associated with increases in hydrophobicity, which occurred as hydrophobic protein residues within the interior of the untreated aggregate became revealed upon treatment with ultrasound, and improved interfacial packing at the emulsion droplet interface. O'Sullivan, Park, et al, (2016a) observed a significant reduction in the hydrodynamic volume of potato protein isolate which is associated to an increase in the hydrophobicity of proteins (Khan, et al, 2012), accounting for the observed enhancements in emulsion formation and stability in this instance. In addition, ultrasound treatment of whey protein Gülseren, et al, 2007), soy protein Hu, et al, 2013), black bean protein and egg white protein increased the hydrophobicity, and the rate of protein adsorption to and interfacial packing at the oil-water interface, as measured by interfacial tension.…”
Section: Emulsifying Effects Of Ultrasonic Processingmentioning
confidence: 89%
“…Indeed, the viscosity of a protein depends on its conformation and thus on its level of hydration, which are a result of the amount of hydrophobic side chains that are buried in the interior of the protein micelles in solution. Khan et al, (2012) also reported that a decrease in intrinsic viscosity led to the dehydration of amphiphilic biopolymer micelles, increased the hydrophobicity of the biopolymer and hence reduced the energy required for the adsorption of amphiphilic biopolymers at the oil-water interface. Therefore, the reduction in intrinsic viscosity of the proteins induced by the ultrasound treatment (cf.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Furthermore, the significant increase in the hydrophobicity of the sonicated NaCas and WPI with the decrease in intrinsic viscosity (cf. Table 4; Khan, Bibi, Pervaiz, Mahmood, & Siddiq, 2012;Tanner & Rha, 1980) would also be expected to lead to a faster adsorption of the proteins to the oil-water interface, thus reducing interfacial tension and facilitating droplet break-up. However, it appears that the rate of adsorption to the interface of sonicated NaCas and WPI remains unchanged despite the smaller micelle sizes and higher hydrophobicity obtained, in comparison with untreated NaCas and WPI.…”
Section: Comparison Of the Emulsifying Properties Of Untreated And Ulmentioning
confidence: 99%
“…Using the earlier established concepts we have applied the closed association model [22][23][24]. According to this model, for micellization with narrow distribution of aggregation number ( ), the equilibrium between copolymers unimers molecules ( ) and micelles ( ) can be written as [24,27]…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of copolymers/surfactant is taken in mole dm −3 and is the equilibrium constant. Hall in his detailed study showed that when the association number is very large, (1) becomes [27] = 1 aq ,…”
Section: Resultsmentioning
confidence: 99%